JTAG and Chip-Off Technologies in Computer Forensics - A. N. Yakovlev; A. S. Danilova (Теория и практика судебной экспертизы, 2018)
The article focuses on the issue of damaged handheld device data extraction with the help of JTAG and Chip-Off technologies. Practical experiments were conducted to extract data from an HTC Wildfire S phone using the JTAG interface and from a BQ S-4525 Vienna phone using the Chip-Off technology. Also discussed are the knowledge and skills required for successful application of these methods by practitioners.